Two unknown species of Mollusca Gastropoda from the Archipelago Fernando de Noronha (Brazil), with description of a new species belonging to the genus Phidiana Gray, 1850 and a new record of Dendrodoris senegalensis Bouchet, 1975 - Francisco J. García; Jesús S. Troncoso (Scientia Marina, 2003)
The Brazilian Archipelago of Fernando de Noronha lies off Cape Sao Roque, State of Rio Grande do Norte, about 195 nautical miles offshore. Only a few faunistic lists of this tropical archipelago have been published, and only four species of Gastropoda Opisthobranchia were cited. In this paper two species of Opisthobranchia Nudibranchia are recorded from this Archipelago. Dendrodoris senegalensis Bouchet 1975, known from Cape Verde and Senegal, amplifies its extension range toward the Western Atlantic. The brazilian specimens differ from the African specimens, in the presence of a completely white branchial tuft. Phidiana riosi sp nov clearly differs from other co-generic species in its colour pattern, having a red ground colour, with numerous white spots scattered on the dorsum. The rhinophores are orange and the cerata white with the cnidosac orange. Internally, this species has jaws with a single row of denticles, and the radular teeth have a central cusp with 7-8 denticles each side. The penis is armed with a black spine and the seminal receptacle connects with two independent ducts, the oviduct and the vaginal duct. Both species are compared with other similar taxa.